2020
DOI: 10.1002/jlb.2ab0420-646r
|View full text |Cite
|
Sign up to set email alerts
|

Differential interferon-γ production by naive and memory-like CD8 T cells

Abstract: CD8 T cells play a crucial role in immune responses to virus infections and tumors. Naïve CD8 T lymphocytes after TCR stimulation undergo differentiation into CTLs and memory cells, which are essential sources of IFN-. We investigated IFN-production by CD8 T cell subsets found in nonimmune mice. A minor fraction of in vitro TCR-stimulated CD8 T cells produce IFN-, and it is regulated at the transcriptional level. Antigen inexperienced C57BL/6 mice present the coexistence of 2 populations. The main population e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Tumor-infiltrating CD8 + T cells are among the most abundant producers of IFNγ and critically contribute to antitumor immunity [ 17 19 ]. Thus, a great deal of tumor-associated immunomodulatory strategies aim to alter CD8 + T-cell functions.…”
Section: Cellular Sources Of Ifnγ In the Colorectal Cancer Microenvironmentmentioning
confidence: 99%
“…Tumor-infiltrating CD8 + T cells are among the most abundant producers of IFNγ and critically contribute to antitumor immunity [ 17 19 ]. Thus, a great deal of tumor-associated immunomodulatory strategies aim to alter CD8 + T-cell functions.…”
Section: Cellular Sources Of Ifnγ In the Colorectal Cancer Microenvironmentmentioning
confidence: 99%
“…3 A and C ). We further examined the memory T cell subpopulation, defined as CD62L-low–expressing T cells ( 17 ), because they more potently contribute to the immune response by producing IFNγ as an example ( 29 , 30 ). EpOME reduced apoptosis in unstimulated memory T cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that inducing CTL activity could be effective in subverting T. b. gambiense infection as evidence suggested that CTL can directly target and destroy extracellular parasites ( [85] . Moreover, CD8 + constitutes a major source of IFN-γ [86] , which is equally essential for resisting T. brucei gambiense infection [87] . Several groups have previously used this approach [14] , [19] , [88] , [89] to assemble antigenic epitopes from different pathogens.…”
Section: Discussionmentioning
confidence: 99%